1997
DOI: 10.1159/000266442
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Aspects of Formant Frequency and Bandwidth in Infants and Toddlers

Abstract: Average formant frequency and formant bandwidth values are reported in a cross-sectional sample of 20 children between 4 and 25 months of age. With the exception of a slight rise in F1 at 18 months of age, average F1 and F2 values changed little during the time period, while the average bandwidths for F1 (B1) and F2 (B2) were found to significantly decrease as age increased. The pattern observed for both average formant frequencies an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 15 publications
2
21
1
Order By: Relevance
“…Our findings of a decrease in formant frequencies with age is not consistent with the earlier findings of Gilbert et al ͑1997͒ andRobb et al ͑1997͒ who found that F1 and F2 remained stable across age. This difference in findings across studies may be accounted for by utterance selection.…”
Section: B Cross-linguistic Differencescontrasting
confidence: 99%
See 4 more Smart Citations
“…Our findings of a decrease in formant frequencies with age is not consistent with the earlier findings of Gilbert et al ͑1997͒ andRobb et al ͑1997͒ who found that F1 and F2 remained stable across age. This difference in findings across studies may be accounted for by utterance selection.…”
Section: B Cross-linguistic Differencescontrasting
confidence: 99%
“…In addition to being consistent with previous findings ͑e.g., Buhr, 1980;Gilbert et al, 1997;Kent and Murray, 1982;Robb et al, 1997;Rvachew et al, 1996͒, these changes are a predictable consequence of developmental changes in the infant's ability to control tongue tip, tongue body, and tongue dorsum position, independently of jaw height, as indicated by the simulations reported in experiment 2 and shown in Table I, when comparing the limited and full range simulations.…”
Section: A Developmental Changesmentioning
confidence: 89%
See 3 more Smart Citations